2017
DOI: 10.1002/ps.4659
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the genomic landscape surrounding the 5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS) gene in glyphosate‐resistant Amaranthus palmeri from geographically distant populations in the USA

Abstract: EPSPS cassettes from distant resistant populations were nearly homologous. Considering the complexity of the cassette, and the degree of similarity among some cassette sequences, the results are consistent with the hypothesis that glyphosate resistance probably evolved once and then rapidly spread across the USA. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…300 kb, causes a genome size increase of about 10% in glyphosate‐resistant plants with 100 EPSPS gene copies (Molin et al ., ). The few polymorphisms in the flanking sequences to the EPSPS locus suggest that the EPSPS cassette has been subjected to little or no recombination and is probably the result of a selection sweep that led to its fixation in many glyphosate‐resistant A. palmeri populations (Gaines et al ., ; Molin et al ., ,b). In support of this speculation is the fact that the amplified EPSPS cassette includes genes linked to environmental stress (e.g.…”
Section: Evolutionary Rescue Of Fitness Costsmentioning
confidence: 99%
“…300 kb, causes a genome size increase of about 10% in glyphosate‐resistant plants with 100 EPSPS gene copies (Molin et al ., ). The few polymorphisms in the flanking sequences to the EPSPS locus suggest that the EPSPS cassette has been subjected to little or no recombination and is probably the result of a selection sweep that led to its fixation in many glyphosate‐resistant A. palmeri populations (Gaines et al ., ; Molin et al ., ,b). In support of this speculation is the fact that the amplified EPSPS cassette includes genes linked to environmental stress (e.g.…”
Section: Evolutionary Rescue Of Fitness Costsmentioning
confidence: 99%
“…5 Eight of the research papers in this issue are on evolved glyphosate resistance. [6][7][8][9][10][11][12][13] Two of these are on a new mechanism of resistance -the "phoenix phenomenon", in which the parts of the plant that directly receive glyphosate spray are rapidly killed, preventing translocation of glyphosate to meristems from which the plant regrows (like a phoenix). 6,7 The cover of this issue illustrates the phenomenon.…”
Section: Glyphosate: the World's Most Successful Herbicide Under Intementioning
confidence: 99%
“…6,7 The cover of this issue illustrates the phenomenon. Molin et al 11 provide evidence for the big question: whether glyphosate target site (5-enolpyruvylshikimate-3-phosphate synthase; EPSPS) gene amplification occurred once and spread in GR Amaranthus palmeri or evolved separately in the many places where it has wreaked havoc. Their evidence supports the hypothesis that it spread from a single case of evolved resistance.…”
Section: Glyphosate: the World's Most Successful Herbicide Under Intementioning
confidence: 99%
“…Follow‐up research has not yet elucidated the mechanism by which such amplification has occurred in Palmer amaranth, although the amplified region is now known to be surprisingly large (possibly >300 kb) and contains multiple genes in addition to EPSPS . A very recent report found that numerous, geographically separated populations contained the same amplicon, suggesting that such amplification is a rare event and may have occurred only once in Palmer amaranth …”
mentioning
confidence: 99%
“…4 A very recent report found that numerous, geographically separated populations contained the same amplicon, suggesting that such amplification is a rare event and may have occurred only once in Palmer amaranth. 5 EPSPS amplification has since been found in glyphosate-resistant biotypes of several additional species, including both grass and broadleaf weeds (e.g., Lolium perenne, Amaranthus tuberculatus, and Kochia scoparia). 6 -8 Cytogenetic analysis has revealed differences in the patterns of gene amplification among species.…”
mentioning
confidence: 99%